Multidisciplinary and personalized approach to the management of mycosis fungoides with chlormethine gel: a collection of clinical experiences - Silvia Alberti Violetti; Marco Ardigò; Paolo Fava; Giuseppe Gritti; Erika Morsia; Francesco Onida; Marco Paulli; Alessandro Pileri; Pietro Quaglino; Serena Rupoli; Miriam Teoli; Pamela Vezzoli (BioExcel Publishing Ltd, 2024)
Topical chlormethine (CL) gel formulation was approved by the EMA in 2017 for the treatment of adult patients with mycosis fungoides (MF). To expand the knowledge on the management of patients with MF, this paper provides an overview of clinical practice evidence about the MF diagnostic phase and a collection of clinical experiences to better characterize the use of CL gel in daily practice. Collected cases underline the importance of the concomitant biopsy and clinical evaluation in the diagnostic phase, with the contribution of a multidisciplinary team and support the use of CL gel as a first-line or adjuvant treatment in selected patients.